Influence of thiamine injections on the folic acid balance in white rats organism - M. Gynznu; K. Nikolaienko; N. Telpis; D. Morozova; A. Viroliubova (Kazimierz Wielki University, 2017)
The interaction of thiamine and folic acid in the organism of white rats were carried out under intramuscular injections of thiamine. The research was conducted on 120 white Wistar rats weighing 150-200 g, which were divided into two groups, one was injected with thiamine, and the second was a control group. All animals were obtained the standard ration of the vivarium. After intramuscular injections of thiamine in dose 1 mg/kg mass it was established, that folic acid content after 60-240 min after injection decrease in small intestine and muscles of animals. Meanwhile, this indication in liver and blood increased. These data achieve that thiamine injection leads to changes of folic acid content in different tissues